Validating a Measure of Perceived Parent–Child Political Socialization. (September 2020) - Pedraza, Francisco I.; Perry, Brittany N.
A growing body of research in political science is influenced by conceptual advances in socialization theory which posit that children can influence adults' learning across a wide range of topics. The concept of bidirectional influence describes socialization led by one's parents and children. One outstanding need in the effort to import this concept to political socialization research is a measure that captures the influence of both parents and children. We meet this need with a measure of relative influence from both parents and children as sources for political learning. We provide evidence of measurement validity using separate samples of Asians, Blacks, Latinos, and Whites. Our findings suggest that our metric is portable across groups, and that the range of what individuals recall about their familial socialization experience includes more child-to-parent influence than existing studies suggest.